Analisis Usability pada Prototipe Self-Service Kiosk untuk Transformasi Digital Industri Percetakan - Elvan Putra Pratama Ramanovanda; Yoga Putra Pratama (Lembaga Pengembangan Kinerja Dosen, 2025)
The printing industry is undergoing a significant digital transformation to overcome traditional operational challenges. Conventional printing services often face problems such as long customer queues, miscommunication regarding technical specifications, and high dependency on staff, leading to operational inefficiencies. To address these issues, a self-service kiosk prototype was designed using the Design Thinking method, aimed at automating and simplifying the ordering process. This study conducts a usability analysis of the kiosk prototype to evaluate its effectiveness, efficiency, and user satisfaction. The method used is Usability Testing, employing performance measurement techniques to assess effectiveness and efficiency, and the Questionnaire for User Interface Satisfaction (QUIS) to evaluate user satisfaction. The results of the Usability Testing indicate that the self-service kiosk prototype achieves a high level of effectiveness and efficiency, meeting the established standards. Furthermore, the analysis of user satisfaction through the QUIS questionnaire shows an optimal outcome, suggesting that the designed interface is well-received by users.